Effects of cyanobacterial biomass on the Japanese quail - Skocovska, B; Hilscherova, K; Babica, P; Adamovsky, O; Bandouchova, H; Horakova, J; Knotkova, Z; Marsalek, B; Paskova, V; Pikula, J (Toxicon, 2007)
Mortality of wild aquatic birds has recently been attributed to cyanobacterial toxins. Despite this, no experimental studies on the effects of defined doses of microcystins administered orally to birds exist. In this experiment, four groups of male Japanese quails daily ingesting 10ml of Microcystis biomass containing 0.045, 0.459, 4.605 or 46.044mug of microcystins, respectively, for 10 and 30 days, showed no mortality. Histopathological hepatic changes in birds after the biomass exposure included cloudy swelling of hepatocytes, vacuolar dystrophy, steatosis and hyperplasia of lymphatic centres. On subcellular level, shrunken nuclei of hepatocytes containing ring-like nucleoli, cristolysis within mitochondria and vacuoles with pseudomyelin structures were present. Vacuolar degeneration of the testicular germinative epithelium was found in two exposed males. Statistically significant differences in biochemical parameters were on day 10 of exposure only. They comprised increased activities of lactate dehydrogenase and a drop in blood glucose in birds receiving the highest dose of the biomass. Principal component analysis revealed a pattern of responses in biochemical parameters on day 10 that clearly separated the two greatest exposure groups from the controls and lower exposures. The results indicate that diagnosis of microcystin intoxication solely based on clinical biochemical and haematological parameters is hardly possible in birds.
Keywords: biomasa; mikrocystiny; Male; Microcystins; Cyanobacteria; Biomass; Mitochondria, Liver; mužské pohlaví; sinice; elektronová mikroskopie; jaterní mitochondrie; Animals; Toxicity Tests; zvířata; testy toxicity; Microscopy, Electron; Bacterial Toxins; Coturnix; bakteriální toxiny